Epstein–Barr virus induction of the Hedgehog signalling pathway imposes a stem cell phenotype on human epithelial cells. Issue 3 (9th October 2013) - Port, Rebecca J; Pinheiro‐Maia, Sonia; Hu, Chunfang; Arrand, John R; Wei, Wenbin; Young, Lawrence S; Dawson, Christopher W
Abstract Nasopharyngeal carcinoma (NPC) is a cancer common in southern China and South East Asia that is causally linked to Epstein–Barr virus (EBV) infection. Here, we demonstrate that NPC displays frequent dysregulation of the Hedgehog (HH) pathway, a pathway implicated in the maintenance of stem cells, but whose aberrant activation in adult tissues can lead to cancer. Using authentic EBV‐positive carcinoma‐derived cell lines and nasopharyngeal epithelial cell lines latently infected with EBV as models for NPC in vitro, we show that EBV activates the HH signalling pathway through autocrine induction of SHH ligand. Moreover, we find that constitutive engagement of the HH pathway induces the expression of a number of stemness‐associated genes and imposes stem‐like characteristics on EBV‐infected epithelial cells in vitro. Using epithelial cells expressing individual EBV latent genes detected in NPC, we show that EBNA1, LMP1, and LMP2A are all capable of inducing SHH ligand and activating the HH pathway, but only LMP1 and LMP2A are able to induce expression of stemness‐associated marker genes. Our findings not only identify a role for dysregulated HH signalling in NPC oncogenesis, but also provide a novel rationale for therapeutic intervention. Copyright © 2013 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.